2019
DOI: 10.1080/14756366.2019.1580276
|View full text |Cite
|
Sign up to set email alerts
|

Delivering bioactive cyclic peptides that target Hsp90 as prodrugs

Abstract: The most challenging issue facing peptide drug development is producing a molecule with optimal physical properties while maintaining target binding affinity. Masking peptides with protecting groups that can be removed inside the cell, produces a cell-permeable peptide, which theoretically can maintain its biological activity. Described are series of prodrugs masked using: (a) O -alkyl, (b) N -alkyl, and (c) acetyl groups, and their binding affinity for Hsp90. Alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Further investigation confirmed that the identity of the binding region was a MEEVD motif in the C-terminus. LB76 restrains the protein-folding function of HSP90, thus blocking protein-protein interactions between HSP90 and co-chaperones (113,114). A de novo delivery system for LB76 produced by polymer nanoparticles and functioning by delivering LB76 into cells and releasing them in a pH-responsive manner, displayed improved inhibitory activity (115).…”
Section: Old and New Anti-neoplastic Treatments Targeting Hsp90mentioning
confidence: 99%
“…Further investigation confirmed that the identity of the binding region was a MEEVD motif in the C-terminus. LB76 restrains the protein-folding function of HSP90, thus blocking protein-protein interactions between HSP90 and co-chaperones (113,114). A de novo delivery system for LB76 produced by polymer nanoparticles and functioning by delivering LB76 into cells and releasing them in a pH-responsive manner, displayed improved inhibitory activity (115).…”
Section: Old and New Anti-neoplastic Treatments Targeting Hsp90mentioning
confidence: 99%
“…For example, in a study of cyclic RGD peptides by Kessler et al, , masking of the arginine side chain with a carbamate and the aspartic acid with an ester was shown to improve cell permeation. Similarly, masking of a lysine residue with methyl groups improved permeation of cyclic pentapeptides targeting HSP60 …”
Section: Can Bro5 Permeation Be Improved By Making Prodrugs?mentioning
confidence: 99%
“…Similarly, masking of a lysine residue with methyl groups improved permeation of cyclic pentapeptides targeting HSP60. 46 Compared to small molecules and peptides, bRo5 compounds have high MWs and larger numbers of HBAs and HBDs. In this case, the addition of masking groups to HBDs could conceivably assist permeation.…”
mentioning
confidence: 99%
“…Acetyl groups are also frequently used to mask alcohols, phenols, and amines in order to improve drug pharmacokinetics, [97] and the acetyl group on aspirin must be cleave by esterases in order to reveal the active drug [98] . Using commercially available liver microsomes the O‐ and N‐dealkylation processes of LB55 were evaluated [99] and after 180 minutes it was clear from the LCMS that there was no dealkylation [100] . Since O‐ and N‐dealkylation processes failed upon treatment with liver enzymes designed to unmask these groups, acetyl groups were investigated, where esterases are readily available in these enzymes.…”
Section: Chemical Strategies For Optimizing the Cell Permeability Of mentioning
confidence: 99%